Analisis Kinerja Konselor dalam Melaksanakan Kegiatan Pendukung BK SMA Negeri se-Kabupaten Banyumas - Putri, Puput Desiana; Nusantoro, Eko; Saraswati, Sinta (Universitas Negeri Semarang, 2014)
The research objective is to analyzing the performance of counselors in implementing the guidance and counseling support activities which includes the planning, implementation and evaluation of senior high schools in Banyumas. The population of this research is senior high school Banyumas. The sampling technique used is cluster random sampling and 6 senior high schools were selected as sample with the number of respondents 27 counselors. Data collection methods on this research using questionnaire instrument with 85 items and was supported by the documentation information. The analysis methods in research using descriptive percentages. Concluded that the performance of counselors in implementing the support activities of guidance and counseling including on good criteria.